Kingdom. 1 - Hara, Yasuhisa, 1975- (VIZ Media, LLC, 2025)
Xin is a war orphan in a poor village in the kingdom of Qin. He has big dreams of becoming a great general, and when his best friend's life is cut short by political machinations, Xin sets off to find a deposed ruler and help restore his place on the throne, while working his way up through the ranks of the Qin kingdom's army to do what no one has ever done before--unify China. Xin's journey begins when his friend Piao, another war orphan who imparts to Xin the same dream of becoming the Greatest Generals Under the Heavens, is offered a position in court in the capital. He leaves Xin behind to train on his own, and to meet him there one day. One fateful night, Piao returns bloodied and on the brink of death, with his dying words being for Xin to go meet a boy who turns out to look exactly like Piao. But this is no ordinary boy--it's the king of Qin, Ying Zheng! And assassins are hot on his tail!--Amazon.